Bidirectional approach for university management: improved relationship with students and educational costs management - Florea, Nicoleta Valentina; Paschia, Liliana; Coman, Dan Marius; Ionescu, Constantin Aurelian; Coman, Mihaela Denisa; Ene, Corina Maria; Gudanescu Nicolau, Nicoleta Luminita (Journal of Business Economics and Management, 2021)
The research, through a bidirectional approach, aims to develop the university management of the degree programs in order to attract and maintain the potential students, as well as to estimate and manage the costs of the educational services offered during their life cycle. The authors bring into the centre of the study the importance of the simulation process in predicting a possible future and reduce the probable risks and costs from time. The results confirm that the simulation methods used help the universities to determine the future risks and to predict when and what relationship marketing programs to use in order to attract, maintain and grow the number of valuable students and also to ensure cost-effective management of university programs.